Faktor Penentu Kepuasan Pengguna Layanan Logistik Di E-Commerce - Ridho Bramulya Ikhsan; Ivan Sangkereng (Jurnal Manajemen Transportasi & Logistik (JMTRANSLOG), 2021)
Customer satisfaction is a determinant of the sustainability of the logistics service provider when collaborating with e-commerce platforms. Therefore, it is essential to study the factors that determine customer satisfaction when using goods delivery services more deeply. This study aims to determine the effect of logistics services with dimensions consisting of product availability and quality, delivery, information and complaints on electronic customer satisfaction. The population in this study is the e-commerce users who live in Jabodetabek, with a total sample of 386. The sampling technique used was purposive sampling. Measurement of variables using a questionnaire with a 5-point differential semantic scale. PLS-SEM was used to answer the research hypothesis. As a result, all questionnaire items meet the requirements of high validity and reliability. The seven variables analyzed, namely availability, delivery time, shipping costs, delivery reliability, product quality and condition, consumer complaints and return policies, and information quality, have a significant positive effect on electronic customer satisfaction. The quality of information and complaints is the dominant determining factor in shaping electronic customer satisfaction.